Analyzing Information Sources Through the Lens of the ACRL Framework: A Case Study of Wikipedia - Trudi E. Jacobson (Communications in Information Literacy, 2020)
Might the ACRL Framework for Information Literacy for Higher Education be used to analyze information resources? Would a Framework-focused analysis of one commonly used resource, Wikipedia, yield valuable insights for the teaching and learning of key information literacy concepts? Each of the six frames is explored in the light of Wikipedia, and metaliteracy, a founding principle of the Framework, is introduced when it provides additional scaffolding in connection with the goals of a particular frame as a way to enhance student learning opportunities. There are a number of components in Wikipedia that align with the Framework, many of which are associated with its structure and community of editors. The idea of connecting information sources with the Framework is being offered as a conversation starter and as a potential mechanism for thinking of the Framework more broadly.